PENGARUH MODEL COOPERATIVE LEARNING TIPE STAD DENGAN MEDIA PEMBELAJA RAN WAYGROUND TERHADAP KETERAMPILAN BERHITUNG SISWA PADA MATERI PERKALIAN KELAS IV DI SD SWASTA WAHANA HARAPAN BANGSA - Tri Apriani; Lili Yanti; Haris Rosdianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low numeracy skills of students in the multiplication material shown from the results of the pre-research, where most of the students have not reached the Minimum Completeness Criteria (KKM). This study aims to determine the influence of the Student Teams Achievement Division (STAD) type cooperative learning model with the help of Wayground learning media on the numeracy skills of grade IV students at Wahana Harapan Bangsa Private Elementary School Singkawang. This study uses a quantitative approach with a pre-experimental method through a one group pretest-posttest design. The research sample amounted to 14 students who were selected using saturated sampling techniques. The instruments used were in the form of numeracy skills tests (pretest and posttest) and student response questionnaires. The data analysis technique used the normality test and the paired sample t-test. The results showed that there was an increase in students' numeracy skills after the application of the STAD model with Wayground media, which was shown by the average score of the posttest was higher than the pretest and the results of the statistical test showed a significant influence. In addition, students' responses to learning are classified as very positive in terms of attention, relevance, satisfaction, and confidence. Thus, it can be concluded that the application of the STAD-type cooperative learning model with Wayground media has a significant effect on improving students' numeracy skills in multiplication materials.